2022
DOI: 10.1007/s40123-022-00474-2
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Versus Retropupillary Iris-Claw Intraocular Lens: Indications, Visual Outcome and Postoperative Complications

Abstract: Introduction:In cases of inadequate capsular support for intraocular lens (IOL) implantation, iris-claw IOL is a practical option. Iris-claw IOL can be implanted anteriorly or retropupillary. In this study, we compare the outcome of implantation of iris-claw IOL between anterior and retropupillary locations. Methods: We retrospectively examined the characteristics and outcomes of patients who underwent iris-claw ''Artisan Ò '' intraocular lens implantation (IOL) during the period of January 2014 to July 2020. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Furthermore, high IOP readings or the prolonged use of postoperative antiglaucoma agents were associated much more in the anterior location (28% vs. 13.1%, P = 0.019). 6 This was not quite in line with our study, although it is worth pointing out that included studies were mostly of anterior placement rather than posterior in the pediatric population in this review. With this, there is not enough evidence regarding the differences between the placement of iris-claw in children to draw a conclusion, and both seem to offer similar efficacy and safety profiles.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Furthermore, high IOP readings or the prolonged use of postoperative antiglaucoma agents were associated much more in the anterior location (28% vs. 13.1%, P = 0.019). 6 This was not quite in line with our study, although it is worth pointing out that included studies were mostly of anterior placement rather than posterior in the pediatric population in this review. With this, there is not enough evidence regarding the differences between the placement of iris-claw in children to draw a conclusion, and both seem to offer similar efficacy and safety profiles.…”
Section: Discussionsupporting
confidence: 64%
“…Iris-claw IOLs have promising features due to its ease of technique and comparable outcomes to other options in adult studies. Safety and efficacy of iris-claw IOL implants in adults are thoroughly studied, 3 4 5 6 however, such studies in the pediatric population are limited. This review aimed to elucidate current evidence regarding the use of iris-claw IOL in terms of its efficacy and safety in the population of pediatric ectopia lentis.…”
Section: Introductionmentioning
confidence: 99%
“…Complications included wound dehiscence, IOL decentration, iris tissue dehiscence, increased intraocular pressure, hyphema, and cystoid macular edema. Al Dwairi compared retropupillary and anterior chamber Artisan IOL implantation and found that the visual outcomes were superior in the retropupillary group and the rate of complications was higher in the anterior chamber group [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The haptics are enclavated to the mid-peripheral iris stroma, and the lens was initially created for surgical correction of phakic myopic eyes, so it minimally interferes with the normal movement of the pupil. Reduced dispersion of iris pigment epithelium, a potential cause of chronic ocular inflammation [3] , is one benefit of this novel design. In a long-term comparison with Gabor's sutureless SFIOL placement technique, Madhivanan et al [4] found that this method produced better results.…”
Section: Introductionmentioning
confidence: 99%